HUBUNGAN POLA MAKAN TERHADAP KEADAAN STATUS GIZI PADA MASYARAKAT WILAYAH PESISIR KAMPUNG NELAYAN - Syahfina Agustin Purba; Fahmi Tegar; Mutiara Hafidzah Tri Haryani; Indi Anggesti; Devi Rani Said Putri; Cindy Claudia; Halima Sadia; Muhammad Iqbal Amin; Ardiansyah Pratama Sitorus; Arja Adi Jaya Pohan; Muhammad Rajasyah Siagian; Syahfina Agustin; Delfriana Ayu (Jurnal Ilmiah Wahana Pendidikan, 2023)
Coastal communities who live on small islands and are isolated in their daily lives are likely to be exposed to health risks, including the lack of availability of quality clean water and the lack of availability of nutritious food. Poor nutritional status due to consumption of inappropriate food. This study aims to determine the relationship between consumption patterns and nutritional problems in coastal communities of fishing villages. This study used a quantitative method with a cross sectional approach. This research was conducted in Fishermen's Village, Medan Belawan District, Medan City with a sample of 34 respondents. Data was collected by measuring food consumption patterns with the Food Frequency Questionnaire and nutritional status from the results of BMI calculations and various daily food consumption patterns, then data were analyzed using Chi-Square to find out the relationship between these studies. From the research results of 34 respondents, there were 16 respondents (47.1%) who had consumption patterns in the good category. Adequate and insufficient consumption patterns respectively by 9 respondents (26.5%). Most of the respondents had normal nutritional status, namely 11 respondents (32.4%). there is a significant relationship between Dietray habit and the nutritional status of the community